Histopathologic findings in malignant peripheral nerve sheath tumor predict response to radiotherapy and overall survival. Issue 1 (1st October 2020) - Lucas, Calixto-Hope G; Vasudevan, Harish N; Chen, William C; Magill, Stephen T; Braunstein, Steve E; Jacques, Line; Dahiya, Sonika; Rodriguez, Fausto J; Horvai, Andrew E; Perry, Arie; Pekmezci, Melike; Raleigh, David R
Abstract: Background: Malignant peripheral nerve sheath tumor (MPNST) is an aggressive and poorly understood malignant neoplasm. Even in the setting of multimodal therapy, the clinical course of MPNST is frequently marked by metastatic conversion and poor overall prognosis, with optimal treatment paradigms for this rare tumor unknown. Methods: We reviewed the medical records and histopathology of 54 consecutive patients who were treated at University of California San Francisco between 1990 and 2018. Results: Our cohort consisted of 24 male and 30 female patients (median age 38 years). Fédération Nationale des Centres de Lutte Contre Le Cancer (FNCLCC) sarcoma grading criteria segregated patients into groups with differences in overall survival (OS) ( P = .02). Increasing Ki-67 labeling index was associated with poor OS (hazard ratio [HR] 1.36 per 10%, P = .0002). Unsupervised hierarchical clustering-based immunohistochemical staining patterns identified 2 subgroups of tumors with differences in H3K27me3, Neurofibromin, S100, SOX10, p16, and EGFR immunoreactivity. In our cohort, cluster status was associated with improved locoregional failure-free rate ( P = .004) in response to radiation. Conclusions: Our results lend support to the FNCLCC sarcoma grading criteria as a prognostic scheme for MPNST, although few cases of grade 1 were included. Further, we identify increased Ki-67 labeling as a strong predictor of poor OS from MPNST. Finally, we identify a subset of MPNSTs with a predictive immunohistochemical profile that has improved local control with adjuvant radiotherapy. These data provide insights into the grading and therapy for patients with MPNST, although further studies are needed for independent validation.